Proposition for Research Activities in the Area of Maritime Transport in the Republic of Slovenia - Počuča, Milojka (Promet - Traffic&Transportation, 2012)
The paper shows the maritime system of the Republic ofSlovenia and its weakpoints, mainly as a result of the transitionand gaining of independence. The second heading describes researchactivities in the area of the maritime system of the Republicof Slovenia during the period from 1992 to 1995. Thethird heading gives a brief review of the EU maritime policy anddescription of Research & Development projects that are intendedas guidelines of the EU maritime policy. In conclusion,the author presents a proposal of the themes and procedures ofscientific research projects in the area of maritime activities ofthe Republic of Slovenia.